Perilaku Politik Masyarakat dalam Pemilihan Kepala Desa Krembangan, Kecamatan Taman, Kabupaten Sidoarjo - Suyono Suyono; Mayta Nur Azizah; Taris Puteri Oktaviani; Flavintus Risando; Efrandi Arnoldus Sandur; Ermelinda Wamul; Marsela Keventina Iwas (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The research aims to analyze the political behavior of the community in the Village Head Election (Pilkades) in Krembangan Village, Taman District, Sidoarjo Regency. The Regional Elections as a manifestation of people's sovereignty are an important object in understanding the political participation of the community at the village level. The research uses a qualitative approach with data collection techniques in the form of in-depth interviews and participatory observation. The subject of the study is the people of Krembangan Village who are directly involved in the Pilkades. The results of the study show that the 2022 Regional Elections in Krembangan Village went smoothly, with active participation from residents who are eligible as voters. Of the 3,000 valid votes, the candidate with number 4, Sutrisno, received the most votes, namely 842 votes, followed by Damri (839 votes), M. Zaini Effendi (645 votes), Akhmad Umar (500 votes), and M. Suherman (174 votes). Factors that affect voting behavior include emotional relationships with candidates, candidates' religious understanding, and social environment. Education level and political awareness also affect participation. Some residents showed their support openly, while others voted privately but remained active. Although participation is quite high, there are still weaknesses such as low campaign quality and lack of public understanding of the candidate's visions and missions.